Freedom: The History and the Future of a Disputed Idea. (December 2022) - Whyte, Jessica
Abstract : Around 1882, the photographer Albert Fernique photographed a group of Parisian workers gathered around trestles and benches inside a workshop. The floor is strewn with piles of wood and the ceiling beams tower above the workmen. Even so, the space is dwarfed by a massive, sculpted shoulder, draped in Roman robes, which dominates the background of the photograph; two workers watching the scene from a beam just below the roof appear to be perched on it like sparrows. The shoulder belonged to the statue, Liberty Enlightening the World— a gift to the United States from the France of the Third Republic. Work on the statue began here, in the workshop of the sculptor Frédéric Auguste Bartholdi, only a year after the suppression of the Paris Commune. More people were killed in that one Bloody Week ( la semaine sanglante ) in 1874 than were executed in the entire Reign of Terror following the French Revolution. If the statue was supposed to symbolize liberty, this was to be an orderly liberty far removed from the license of the armed Parisian workers and their short-lived utopian government. Unlike her ancestor Marianne, immortalized by Eugène Delacroix's Liberty Leading the People, the statue does not wear the red cap that, since ancient Rome, had symbolized freedom from slavery. In the wake of the Paris Commune, the Third Republic banned the cap and sought to banish the unruly freedom it represented.